The UN convention on the law of the sea: an inefficient public good supplied by an inefficient organization - Federico Foders (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1984)
The Convention on the Law of the Sea is the still controversial outcome of the longest and perhaps most expensive international conference of the century. The most debated issue at UNCLOS III was the Convention's regime to govern seabed mining; differences of opinion on this regime have seriously challenged the purpose of the Conference and are likely to keep the Convention from becoming effective as international law. This paper is an inquiry into the economic causes for such an outcome. In Section II the efficieny of the Convention's regulation for minerals production from the ocean bed is analyzed. Section III deals with the efficiency of the Convention's production process at UNCLOS, focusing on the determinants of voting behaviour and on the rules of procedure used. The last section explores the rationale for alternative multilateral organizations for an efficient management of seabed mining.
Keywords: 330